Signatures of Nucleotide Analog Incorporation by an RNA-Dependent RNA Polymerase Revealed Using High-Throughput Magnetic Tweezers - Dulin, David; Arnold, Jamie J.; Van Laar, Theo; Oh, Hyung-Suk; Lee, Cheri; Perkins, Angela L.; Harki, Daniel A.; Depken, Martin; Cameron, Craig E.; Dekker, Nynke H. (Cell Reports, 2017)
RNA viruses pose a threat to public health that is exacerbated by the dearth of antiviral therapeutics. The RNA-dependent RNA polymerase (RdRp) holds promise as a broad-spectrum, therapeutic target because of the conserved nature of the nucleotide-substrate-binding and catalytic sites. Conventional, quantitative, kinetic analysis of antiviral ribonucleotides monitors one or a few incorporation events. Here, we use a high-throughput magnetic tweezers platform to monitor the elongation dynamics of a prototypical RdRp over thousands of nucleotide-addition cycles in the absence and presence of a suite of nucleotide analog inhibitors. We observe multiple RdRp-RNA elongation complexes; only a subset of which are competent for analog utilization. Incorporation of a pyrazine-carboxamide nucleotide analog, T-1106, leads to RdRp backtracking. This analysis reveals a mechanism of action for this antiviral ribonucleotide that is corroborated by cellular studies. We propose that induced backtracking represents a distinct mechanistic class of antiviral ribonucleotides.
EVALuna2:26367